2015
DOI: 10.1021/acs.bioconjchem.5b00193
|View full text |Cite|
|
Sign up to set email alerts
|

Peptidyl–Oligonucleotide Conjugates Demonstrate Efficient Cleavage of RNA in a Sequence-Specific Manner

Abstract: Described here is a new class of peptidyl-oligonucleotide conjugates (POCs) which show efficient cleavage of a target RNA in a sequence-specific manner. Through phosphoramidate attachment of a 17-mer TΨC-targeting oligonucleotide to amphiphilic peptide sequences containing leucine, arginine, and glycine, zero-linker conjugates are created which exhibit targeted phosphodiester cleavage under physiological conditions. tRNA(Phe) from brewer's yeast was used as a model target sequence in order to probe different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(64 citation statements)
references
References 69 publications
3
61
0
Order By: Relevance
“…Over the last couple of decades, some progress has been achieved in the field of designing siteselective artificial ribonucleases [42][43][44][45][46][47][48][49][50][51][52][53][54]. It was shown that short peptides, containing either alternating leucine and arginine residues or imidazole-based catalytic groups, conjugated to antisense oligonucleotides targeting tRNA, were able to hydrolyze linkages adjacent to an oligonucleotide-binding site without involvement of exogenous species such as metal ions, enzymes or cofactors (e.g., RISC, RNase H) [42,44,45,47,50,51].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…Over the last couple of decades, some progress has been achieved in the field of designing siteselective artificial ribonucleases [42][43][44][45][46][47][48][49][50][51][52][53][54]. It was shown that short peptides, containing either alternating leucine and arginine residues or imidazole-based catalytic groups, conjugated to antisense oligonucleotides targeting tRNA, were able to hydrolyze linkages adjacent to an oligonucleotide-binding site without involvement of exogenous species such as metal ions, enzymes or cofactors (e.g., RISC, RNase H) [42,44,45,47,50,51].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…It was shown that short peptides, containing either alternating leucine and arginine residues or imidazole-based catalytic groups, conjugated to antisense oligonucleotides targeting tRNA, were able to hydrolyze linkages adjacent to an oligonucleotide-binding site without involvement of exogenous species such as metal ions, enzymes or cofactors (e.g., RISC, RNase H) [42,44,45,47,50,51]. Effective cleavage of complementary substrates was also demonstrated for tris(2-aminobenzimidazole) ribonuclease conjugated to PNA oligomers [49].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations